X‐ray tomography of tsunami deposits: Towards a new depositional model of tsunami deposits. Issue 2 (28th October 2016) - Falvard, Simon; Paris, Raphaël
Abstract: X‐ray computed microtomography is used to obtain high resolution imagery of a historical tsunami deposit in Andalusia, Spain (1755 Lisbon tsunami). The technique allows characterization of grain‐size distribution, structures, component analysis and sedimentary fabric of fine‐grained unconsolidated tsunami deposits at resolutions down to particle scale. The results are validated by comparing to data obtained using other techniques such as laser diffraction, anisotropy of magnetic susceptibility and X‐ray microfluorescence on the same deposits. Specific technical details such as sampling, scanning and image processing methods, and further improvements are addressed. The use of X‐ray computed microtomography provides new insights into the stratigraphy of the deposits and gives access to significantly more detailed view of key sedimentary features such as mudlines, rip‐up clasts, crude laminations, convolutions, floating outsized clasts and contacts between successive units. This analysis of the 1755 tsunami deposits using X‐ray computed microtomography allows the proposal of new hypotheses for the sedimentary processes forming tsunami deposits. Deposition by settling is limited and the section analysed here is dominated by a high shear stress leading to the development of traction carpets, with laminated mudlines corresponding to the basal frictional region of these carpets. The onset of the tsunami backwash is marked by a micro‐vortex resembling Kelvin–Helmoltz instabilities.